Rozwiąż równanie :
Zad1
A)9+x=1 7/8
C)8a+4=36
D)-3/4-1/4l=2,25
E)-8y=5
F)-2,2+x=6,1
G)8/9k+1/3=3
H)-2,5c-8=17
I)x-4/5=0,8
J)-1/3y=10
K)6b-3=-9
L)0,4m-2=-6
Zad2
A)2(x-1/2)-x+3=3
B)0=(x-1)-(3x-5
C)3(1-x)-(1-2x)=9
D)0=3-(2x+1)
E)(-1/2x+1)+3x/2=3

Zad3
12y-(y+5)=10y-1
-3(y/3+1)-2=4(1-y)
2(u-5)+15=3(u-4)+10
2(3a-2)-6=4,5(2a-1)+1/2

1

Odpowiedzi

2010-04-07T23:13:19+02:00
A)
9+x=1 7/8
x=1⅞-9
x=-7⅛

C)
8a+4=36
8a=36-4
8a=32
a=4

D)
-3/4-1/4l=2,25
-¼l=2,25+¾
-¼l=3
l=-12

E)
-8y=5
y=-⅝

F)
-2,2+x=6,1
x=6,1+2,2
x=8,3

G)
8/9k+1/3=3
⁸/₉k=3-⅓
⁸/₉k=2⅔
k=3

H)
-2,5c-8=17
-2,5c=17+8
-2,5c=25
c=-10

I)
x-4/5=0,8
x=0,8+⅘
x=1,6

J)
-1/3y=10
y=-30

K)
6b-3=-9
6b=-9+3
6b=-6
b=-1

L)
0,4m-2=-6
0,4m=-6+2
0,4m=-4
m=-10

Zad2
A)
2(x-1/2)-x+3=3
2x-1-x+3=3
2x-x=3+1-3
x=1

B)
0=(x-1)-(3x-5
0=x-1-3x+5
-x+3x=-1+5
2x=4
x=2

C)
3(1-x)-(1-2x)=9
3-3x-1+2x=9
-3x+2x=9-3+1
-x=7
x=-7

D)
0=3-(2x+1)
0=3-2x-1
2x=3-1
2x=2
x=1

E)
(-1/2x+1)+3x/2=3|*3
-1,5x+3+4,5x=9
-1,5x+4,5x=9-3
3x=6
x=2


Zad3
12y-(y+5)=10y-1
12y-y-5=10y-1
12y-y-10y=-1+5
y=4


-3(y/3+1)-2=4(1-y)
-y-3-2=4-4y
-y+4y=4+3+2
3y=9
y=3


2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u-3u=-12+10+10-15
-u=-7
u=7


2(3a-2)-6=4,5(2a-1)+1/2
6a-4-6=9a-4,5+½
6a-9a=-4,5+½+4+6
-3a=6
a=-2
2 3 2